2009
DOI: 10.1021/ef900235e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Gasification of Nascent Char in Steam Atmosphere during the Pyrolysis of Na- and Ca-Ion-Exchanged Brown Coals in a Drop-Tube Reactor

Abstract: Several recent studies on in situ steam gasification of coal suggest a possibility of extremely fast steam gasification of char from rapid pyrolysis of pulverized brown coal. The unprecedented rate of char steam gasification can be achieved by exposing nascent char, that is, after tar evolution (temperature range >600°C), but before devolatilization (<900°C), to steam in the presence of Na and/or Ca dispersed in/on the char. In this study, we conducted rapid pyrolysis experiments using ion-exchanged Loy Yang b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Pyrolysis is a process which involves heating matter in an inert atmosphere to produce useful products, with the product properties depending upon various factors (Adam et al 2013, Lago et al 2018, Mašek et al 2009. One of which is the chemical composition of the original biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is a process which involves heating matter in an inert atmosphere to produce useful products, with the product properties depending upon various factors (Adam et al 2013, Lago et al 2018, Mašek et al 2009. One of which is the chemical composition of the original biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Bayarsaikhan et al (2005) found that the inherent Na + and Ca 2+ species increased the initial gasification rate of the nascent char under a steam atmosphere by more than 80 % in a drop-tube/fixed-bed reactor system. Mašek et al (2009) reported that catalytic steam gasification proceeded extensively even under conditions in which the gasification of the unloaded coal was retarded by coexisting tarry compounds and char. In addition, higher AAEM contents have also been shown to be favorable for maintaining the coking activity of the char, promoting the in situ steam reforming of tar over the char surface.…”
Section: In Situ Steam Gasification Of Char Gasificationmentioning
confidence: 99%
“…The gas flow rate was carefully adjusted to maintain a constant gas residence time in the isothermal zone under the different experimental conditions. Detailed descriptions of the experimental setup and procedure are given elsewhere [15,27,28]. The experimental conditions used to investigate the effects of residence time, reaction temperature, steam partial pressure, and solid hold-up on the conversion characteristics of the coal samples in the DTR are provided in Table 1.…”
Section: Drop-tube Reactor Coal Conversion Experimentsmentioning
confidence: 99%